New insights into cortical development and plasticity: from molecules to behavior. Issue 16 (August 2020) - Park, Woon Ju; Fine, Ione
Highlights: The development of gross neuroanatomy precedes experience-dependent plasticity. A cascade of neurochemical and structural events, mediated by experience-driven neural activity, controls the sensitive period. Environmental manipulations, such as sensory deprivation, have an impact on the timeline of the sensitive period. Prolonged sensory deprivation early in development results in cross-modal plasticity. Abstract : The human brain contains 100 billion neurons, and each neuron can have up to 200, 000 connections to other neurons. Recent advancements in neuroscience — ranging from molecular studies in animal models to behavioral studies in humans — have given us deeper insights into the development of this extraordinarily intricate system. Studies show a complex interaction between biological predispositions and environment; while gross neuroanatomy and low-level functions develop early prior to receiving environmental inputs, functional selectivity is shaped through experience, governed by the maturation of local excitatory and inhibitory circuits and synaptic plasticity during sensitive periods early in development. Plasticity does not end with the closing of the early sensitive period – the environment continues to play an important role in learning throughout the lifespan. Recent work delineating the cascade of events that initiates, controls and ends sensitive periods, offers new hope of eventually being able to remediate various clinical conditions by selectively reopening plasticity.